Object in View: Understanding International Students’ Participation in Group Work - Straker, John (Journal of International Students, 2020)
The literature on international student participation in Anglo-Western universities is predicated on an assumption of underachievement. Reductive understandings prevail with English language competence and cultural background highlighted. Drawing from a case study of group work in a first-year module in a management course at an internationalizing university in the United Kingdom, this article explores students’ perceptions of the impact of English language competence on participation. The case study, which aimed at a holistic understanding, adopted an activity theoretical framework for modeling participation and for analyzing focus group data. Four educational objects were identified with the construct “object in view” employed in recognition of the plurality of the object. The in-depth analysis focused on the object. Although focus groups traversed a range of topics, English language competence was widely discussed. However, the analysis suggests that the extent English language was perceived as an issue was relative to the object in view.